The Effect of Pop-Up Books on The Sentence Writing Achievement of The Eighth Grade Students’ of SMPU Al-Anwari Banyuwangi - Intan Tutik Hardiyanti; Tri Mulyati; Abdul Halim (LUNAR, 2019)
This research was an experimental research. The purpose of this research was to measure there is an effect of pop-up books on the sentence writing achievement of the eighth grade students‟ of SMPU Al-Anwari Banyuwangi in the 2017/2018 academic year. The area of this research was SMPU Al-Anwari Banyuwangi. It was chosen purposively because they have never been taught by using „Pop-Up‟ books at this school. Another reason was that the permission to conduct this research in this school from the headmaster has already accepted. The population of this research was all of the eighth grade students of SMPU Al-Anwari Banyuwangi in the 2017/2018 academic year. The total number of the respondents was 48 students, consisting of 24 students of grade VIII A as the experimental group and 24 students of VIII B as the control group. Based on the result of the data analysis of t-test formula, it can be known that value of t-test is higher than that of the t-critical (2,464 > 2,013). It shows that there is a significant effect of pop-up books on the sentence writing achievement of the eighth grade students‟ of SMPU Al-Anwari Banyuwangi in the 2017/2018 academic year. Based on the result, it is suggested that the students to use pop-up books as a guide in writing simple present tense sentences. Further, the English teachers are suggested to apply pop-up book as media in teaching English to improve the students sentence writing achievement and make them understand the lesson, and the future researchers are also suggested to use these results of the research as information or a reference to conduct a further and better research which focuses on the same problem by using different research design, such as a classroom action research to improve the students writing skill especially for English subject.